Do patients prefer optional follow-up for simple upper extremity fractures: A pilot study. Issue 10 (October 2016) - Finger, Abigail; Teunis, Teun; Hageman, Michiel G.; Thornton, Emily R.; Neuhaus, Valentin; Ring, David
Abstract: Introduction: We aimed to evaluate the results of offering patients optional follow-up for simple upper extremity fractures. Specifically this study tested if there is a difference in (1) upper extremity disability, (2) return to work, and (3) satisfaction with delivered care at 2–6 months after enrollment between patients who choose and do not choose a return visit for an adequately aligned metacarpal, distal radius, or radial head fracture. Additionally we assessed if there was a difference in overall evaluation of the visit at enrollment between those patients and what factors were associated with returning after initially choosing not to schedule a follow-up visit. Patients and methods: We prospectively enrolled all adult patients (n = 120) with adequately aligned metacarpal fractures, non-or minimally displaced distal radius fractures, and isolated non- or minimally displaced radial head fractures of whom 82 (68%) were available at 2–6 months after enrollment. Subjects chose to have a scheduled (n = 56) or optional (n = 64) return visit. Subsequently, we recorded patient demographics and overall evaluation of the visit. Between two and six months after enrollment we measured QuickDASH, satisfaction with care, and current employment status. Results: Accounting for potential differences in baseline characteristics by multivariable analysis, return choice was not associated with QuickDASH (β regression coefficient [β] −0.53, 95% confidence interval [CI] −7.4 to 6.4, standard error [SE] 3.5, P = 0.88), return to work (odds ratio [OR] −1.3, 95%CI −3.5 to 0.95, SE 1.1, P = 0.26), satisfaction with care (β −0.084, 95%CI −0.51 to 0.35, SE 0.22, P = 0.70), or overall evaluation of the initial visit (β 0.18, 95%CI −0.38 to 0.73, SE 0.28, P = 0.53). Of the 64 people choosing optional follow-up, 11 patients returned (17%). The only factor independently associated with returning after initially not choosing to return was greater disability at enrollment (OR 1.05, 95%CI 1.0050–1.098, SE 0.024, P = 0.029). Conclusions: A majority of patients prefer optional follow-up for simple upper extremity fractures with a good prognosis. Hand surgeons can consider offering patients with low-risk hand fractures an optional second visit. Eliminating unnecessary visits, tests and imaging could lower the cost of care. Level of evidence: Therapeutic level II.